2021
DOI: 10.3390/cells10102555
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review of Microglia and Monocytes in CNS Phagocytosis

Abstract: Macrophages maintain tissue homeostasis by phagocytosing and removing unwanted materials such as dead cells and cell debris. Microglia, the resident macrophages of the central nervous system (CNS), are no exception. In addition, a series of recent studies have shown that microglia phagocytose the neuronal synapses that form the basis of neural circuit function. This discovery has spurred many neuroscientists to study microglia. Importantly, in the CNS parenchyma, not only microglia but also blood-derived monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 141 publications
(222 reference statements)
0
15
0
Order By: Relevance
“…We observed increased expression of IBA-1 in ONX-0914 treated C20 cells comparison to control DMSO treated cells (Figures 7F, G). b5i/LMP7-deficient primary microglia exhibit increased phagocytic activity despite less activation in response to amyloid-beta Microglia are the resident macrophages of the brain and, as such are responsible for the clearance of apoptotic cells and potentially toxic protein aggregates (1)(2)(3). It is suggested that apoptotic cells and protein aggregates activate microglia to be phagocytosed by them (46).…”
Section: Protein Kinase R Senses B5i/lmp7 Inhibition By Onx-0914 To T...mentioning
confidence: 99%
See 1 more Smart Citation
“…We observed increased expression of IBA-1 in ONX-0914 treated C20 cells comparison to control DMSO treated cells (Figures 7F, G). b5i/LMP7-deficient primary microglia exhibit increased phagocytic activity despite less activation in response to amyloid-beta Microglia are the resident macrophages of the brain and, as such are responsible for the clearance of apoptotic cells and potentially toxic protein aggregates (1)(2)(3). It is suggested that apoptotic cells and protein aggregates activate microglia to be phagocytosed by them (46).…”
Section: Protein Kinase R Senses B5i/lmp7 Inhibition By Onx-0914 To T...mentioning
confidence: 99%
“…Thanks to their capacity of sensing changes in their environment such as pathogens and/or small protein flux perturbations, microglia largely contribute to the surveillance of the central nervous system (CNS) (1)(2)(3). As microglia are in fact macrophages of the brain, they are able to phagocytose protein aggregates and pathogens to clear the environment and protect the brain from possible danger (2)(3)(4). Therefore, microglial function heavily relies on protein homeostasis and mediation of innate immune signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia primarily accomplish this via phagocytosis, a process through which cells recognize, engulf, and digest degraded cellular particles and debris. Following acquired brain injury, microglia are capable of acting as antigen-presenting cells to initiate activation of neighboring T-cells and orchestrate an inflammatory response that can impair proper neurological function [ 14 , 15 , 16 , 17 , 18 , 19 ]. In addition, microglia are activated following brain injury and undergo significant morphological changes to execute different tasks.…”
Section: Distinct Role For Microglia and Other Myeloid Cells In The N...mentioning
confidence: 99%
“…In peripheral immune cells, morphine is repeatedly shown to decreases immune activation and phagocytosis in vivo and in vitro (Rojavin, Szabo et al 1993, Ninković and Roy 2012, Ninkovic, Anand et al 2016) dependent on dose (Borman, Ciepielewski et al 2009) and duration of exposure (Pagán, Figueroa et al 2001). Phagocytosis is an important immune effector that serves to clear damage, debris, and infection (Andoh and Koyama 2021). Unlike peripheral immune cells, the effect of morphine on microglia is less well studied.…”
Section: Introductionmentioning
confidence: 99%